Traffic Monitoring and Analysis First International Workshop, TMA 2009, Aachen, Germany, May 11, 2009. Proceedings - Papadopouli, Maria; Owezarski, Philippe; Pras, Aiko.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2009)
This book constitutes the proceedings of the First International Workshop on Traffic Monitoring and Analysis, TMA 2008, held in Aachen, Germany, on May 11, 2008 in conjunction with the IFIP Networking 2008 conference. The workshop is an initiative from the COST Action IC0703 "Data Traffic Monitoring and Analysis: Theory, Techniques, Tools and Applications for the Future Networks". The 15 papers contained in this volume were carefully reviewed and selected from 34 submissions. They encompass research areas related to traffic analysis and classification, measurements, topology, discovery, detection of specific applications and events, packet inspection, and traffic inference. The papers are organized in topical sections on QoS measurement, rupture detection, traffic classification, as well as traffic analysis and topology measurements.
QoS Measurement -- Realistic Passive Packet Loss Measurement for High-Speed Networks -- Inferring Queue State by Measuring Delay in a WiFi Network -- Network-Wide Measurements of TCP RTT in 3G -- Rupture Detection -- Portscan Detection with Sampled NetFlow -- Automated Detection of Load Changes in Large-Scale Networks -- Passive, Streaming Inference of TCP Connection Structure for Network Server Management -- Traffic Classification -- GTVS: Boosting the Collection of Application Traffic Ground Truth -- TIE: A Community-Oriented Traffic Classification Platform -- Revealing the Unknown ADSL Traffic Using Statistical Methods -- Accurate, Fine-Grained Classification of P2P-TV Applications by Simply Counting Packets -- Detection and Tracking of Skype by Exploiting Cross Layer Information in a Live 3G Network -- Traffic Analysis and Topology Measurements -- Incentives for BGP Guided IP-Level Topology Discovery -- Scaling Analysis of Wavelet Quantiles in Network Traffic -- KISS: Stochastic Packet Inspection -- DTS: A Decentralized Tracing System.
Keywords: Computer science; Computer communication systems; Computer system failures; Information storage and retrieval; Management information systems; Computer Science; Computer Communication Networks; System Performance and Evaluation; Information Systems Applications (incl. Internet).; Information Storage and Retrieval; Management of Computing and Information Systems; Electronic books